Auxin signaling: a big question to be addressed by small molecules. (18th November 2017) - Ma, Qian; Grones, Peter; Robert, Stéphanie
Abstract : This review summarizes the current knowledge of auxin signaling and emphasizes how chemical genomics could help to unravel the complexity of the TIR1/AFB–Aux/IAA co-receptor system. Abstract: Providing a mechanistic understanding of the crucial roles of the phytohormone auxin has been an important and coherent aspect of plant biology research. Since its discovery more than a century ago, prominent advances have been made in the understanding of auxin action, ranging from metabolism and transport to cellular and transcriptional responses. However, there is a long road ahead before a thorough understanding of its complex effects is achieved, because a lot of key information is still missing. The availability of an increasing number of technically advanced scientific tools has boosted the basic discoveries in auxin biology. A plethora of bioactive small molecules, consisting of the synthetic auxin-like herbicides and the more specific auxin-related compounds, developed as a result of the exploration of chemical space by chemical biology, have made the tool box for auxin research more comprehensive. This review mainly focuses on the compounds targeting the auxin co-receptor complex, demonstrates the various ways to use them, and shows clear examples of important basic knowledge obtained by their usage. Application of these precise chemical tools, together with an increasing amount of structural information for the major components in auxin action, will certainly aid in strengthening our insights into the complexity and diversity of auxin response.